AN EVALUATION OF THE MADRASAH TEACHER QUALITY IMPROVEMENT PROGRAM THROUGH PROFESSIONALISM TRAINING BASED ON INDUSTRY 4.0 - sulaeman ali; Kasmah; Sultan Hasanuddin; Al Fikrah; Maleha (Atta'dib Jurnal Pendidikan Agama Islam, 2026)
This study evaluates the Madrasah Teacher Quality Improvement Program through Industry 4.0-based professionalism training at MI Babul Ilmi Lemo Ape, Bone Regency, South Sulawesi, using the Context, Input, Process, Product (CIPP) evaluation model. Data were collected through interviews and observations. The findings indicate that the training was implemented based on teachers’ needs and aligned with the demands of Industry 4.0. Training resources, including materials, instructors, and budget, were adequately prepared, and implementation generally proceeded well, though more practical sessions and follow-up mentoring were needed. The program improved teachers’ ability to utilize digital learning applications such as Kahoot, Quizizz, Canva, and TikTok. However, challenges, including limited student access to mobile devices and unstable internet connectivity, hindered optimal implementation. Teachers addressed these constraints by using PowerPoint and Canva, while further policy support and improved internet infrastructure are needed to enhance program effectiveness.